The teaching of spanish in the schools of País Vasco: Juan María de Eguren (1867-1876) lexicographic work - García Aranda, María Ángeles (Boletín de Filología, 2009)
Juan Maria de Eguren, inspector of education, published a seriesof works between 1867 and 1876 aimed at solving the problemof ignorance of the Spanish in the classrooms of the País Vasco.Eguren's ideas were developped in his Método práctico para enseñarel castellano en las escuelas vascongadas (Vitoria, SeminarioCatólico Vasco-Navarro, 1867), a book which, besides a thematicvocabulary or nomenclature, a few exercises of decline and of verbalflexion and a few practices of translation, includes a prologue and a"Procedimiento que conviene seguir en las escuelas vascongadas paraenseñar el castellano a los niños, y uso que al efecto debe hacerse deeste libro" (pages XI-XXIV). An analysis of the vocabularies anda study of the historical and lexicographical context in which theywere designed and composed is presented in this article.